Tinjauan Hukum terhadap Fenomena Kawin Kontrak dalam Ranah Keperdataan; Urgensi Formulasi Hukum - Vina Yulianti, Hanipah; Hayatul Iman, Candra (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2024)
Ideally, the principles of law, religion, and social norms in Indonesia establish marriage as a long-term bond characterized by mutual respect and responsibility, aimed at forming a harmonious family. However, in reality, contract marriages, which are driven by subjective agreements and have a fixed term, contradict these norms and are not recognized under the Civil Code (KUHPER). This practice results in negative consequences such as pornography, prostitution, human exploitation, trafficking, and domestic violence. This study identifies the discrepancy between the ideal principles and the actual practice of contract marriages and proposes direct criminal sanctions as a more effective solution to address this issue. The research is classified as a qualitative library study. The methodology employed is a normative juridical approach with qualitative descriptive analysis of legal regulations and contract marriage practices. The findings indicate that contract marriages are inconsistent with civil law principles and potentially violate criminal law. Therefore, it is crucial to develop a more comprehensive legal framework by implementing direct criminal penalties, bypassing civil violations. This approach is expected to provide a stronger deterrent effect against perpetrators and reduce the prevalence of contract marriages in Indonesia.